Alkenes from β-lithiooxyphosphonium ylides generated by trapping α-lithiated terminal epoxides with triphenylphosphine - Hodgson, David. M.; Persaud, Rosanne S. D. (Beilstein Journal of Organic Chemistry, 2012)
Terminal epoxides undergo lithium 2,2,6,6-tetramethylpiperidide-induced α-lithiation and subsequent interception with Ph3P to provide a new and direct entry to β-lithiooxyphosphonium ylides. The intermediacy of such an ylide is demonstrated by representative alkene-forming reactions with chloromethyl pivalate, benzaldehyde and CD3OD, giving a Z-allylic pivalate, a conjugated E-allylic alcohol and a partially deuterated terminal alkene, respectively, in modest yields.
Keywords: alkenes; epoxides; lithiation; synthetic methods; ylide